Positive pole piece as well as preparation method and application thereof

By adopting a multi-layer structure in the positive electrode sheet of sodium ion battery, the inner layer uses the first Prussian positive electrode material, the outer layer uses polyanion positive electrode material, and the material formula is optimized, the energy density of the positive electrode material of sodium ion battery is solved. The problem of insufficient thermal stability and cycle stability achieves more efficient battery performance.

CN119230746APending Publication Date: 2024-12-31JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411353978.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The cathode material of sodium ion batteries has problems such as low energy density, insufficient thermal stability and cycling stability, which limits its application.

Method used

The positive electrode sheet adopts a multi-layer structure, the inner layer uses the first Prussian positive electrode material, and the outer layer uses polyanionic positive electrode material, and the formulation of conductive agents and binders is optimized by adjusting the material proportion and adding water absorbents to ensure the material. stability and capacity.

Benefits of technology

The capacity, thermal stability and cycling stability of sodium ion batteries are improved, structural collapse is avoided, and more efficient battery performance is achieved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a positive pole piece and a preparation method and application thereof.The positive pole piece comprises a current collector and a coating arranged on the surface of at least one side of the current collector, and the coating comprises a first active layer arranged on the surface of the current collector; the second active layer is arranged on one side, far away from the current collector, of the first active layer; the first active layer comprises a first Prussian positive electrode material, and the second active layer comprises a polyanion positive electrode material; in the coating, the content of the first Prussian positive electrode material is smaller than that of the polyanion positive electrode material. According to the positive pole piece disclosed by the invention, different types of positive pole materials are used in different active layers, and the content of the first Prussian positive pole material is smaller than that of the polyanion positive pole material, so that the positive pole piece has relatively good thermal stability, cycling stability and capacity at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a positive electrode sheet and a preparation method and application thereof. Background Art

[0002] The principle structure of sodium-ion batteries is similar to that of lithium-ion batteries, and their cost is lower than that of lithium-ion batteries. Therefore, sodium-ion batteries can be used to replace lithium-ion batteries with higher costs. However, the low performance of sodium-ion batteries, such as capacity and stability, is the main factor limiting the application of sodium-ion batteries, and the positive electrode material of sodium-ion batteries is the key to improving the performance of sodium-ion batteries.

[0003] At present, the positive electrode materials of sodium ion batteries mainly include polyanion materials and Prussian blue materials. Among them, polyanion compounds have good ion transport and structural stability, but their energy density is low, while Prussian blue materials have high energy density but low stability.

[0004] Therefore, it is necessary to provide a positive electrode plate that can take into account the capacity, thermal stability and cycle stability of sodium ion batteries. Summary of the invention

[0005] The object of the present invention is to provide a positive electrode plate and a preparation method and application thereof. The positive electrode plate uses different types of positive electrode materials in different active layers, and the content of the first Prussian positive electrode material is less than the content of the polyanion positive electrode material, so that the positive electrode plate can have good thermal stability, cycle stability and capacity at the same time.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a positive electrode plate, the positive electrode plate comprising a current collector and a coating disposed on at least one side of the current collector, the coating comprising a first active layer disposed on the surface of the current collector, and a second active layer disposed on a side of the first active layer away from the current collector;

[0008] The first active layer includes a first Prussian cathode material, and the second active layer includes a polyanion cathode material;

[0009] In the coating, the content of the first Prussian cathode material is less than the content of the polyanion cathode material.

[0010] Preferably, the mass ratio of the first Prussian cathode material to the polyanion cathode material is (1-3):(4-9).

[0011] Preferably, the second active layer further includes a water absorbent.

[0012] Preferably, the mass ratio of the polyanion positive electrode material to the water absorbent is 20:(0.5-2).

[0013] Preferably, the water absorbent includes a second Prussian cathode material.

[0014] Preferably, the mass ratio of the first Prussian positive electrode material to the polyanion positive electrode material is A, the mass fraction of the water absorbent / (the sum of the mass fractions of the first Prussian positive electrode material and the polyanion positive electrode material)×100 is B, and A and B satisfy the following relationship: B=e^[(bA) / a], wherein a is 0.8-0.9, and b is 0.8-1.87.

[0015] Preferably, the thickness ratio of the first active layer to the second active layer is (1-2):(2.25-3).

[0016] Preferably, the first active layer further includes a first conductive agent.

[0017] Preferably, the second active layer further includes a second conductive agent.

[0018] Preferably, the sum of the mass fractions of the first conductive agent and the second conductive agent / (the sum of the mass fractions of the first Prussian positive electrode material and the polyanion positive electrode material)×100 is N, the thickness ratio of the first active layer and the second active layer is M, and M and N satisfy N=e^[(My) / x], wherein x is 0.12-0.13, and y is 0.15-0.25.

[0019] Preferably, the first conductive agent includes any one of graphite, multi-walled carbon nanotubes, graphene, SP or acetylene black, or a combination of at least two thereof, preferably multi-walled carbon nanotubes.

[0020] Preferably, the second conductive agent includes any one of graphite, multi-walled carbon nanotubes, graphene, SP or acetylene black or a combination of at least two thereof, preferably any one of graphite, graphene, SP or acetylene black or a combination of at least two thereof.

[0021] Preferably, the first active layer further includes a first binder.

[0022] Preferably, in the first active layer, the mass ratio of the first Prussian cathode material, the first conductive agent and the first binder is (10-40):(0.5-2):(0.3-1.2).

[0023] Preferably, the second active layer further includes a second binder.

[0024] Preferably, in the second active layer, the mass ratio of the polyanion positive electrode material, the second conductive agent and the second binder is (60-90):(2.4-3.6):(1.2-1.8).

[0025] Preferably, the first Prussian positive electrode material includes any one or a combination of at least two of a Prussian white material, a Prussian blue material, a composite material of Prussian blue and activated carbon, a composite material of Prussian blue, chitosan and nanogold, and a composite material of Prussian blue, graphene and carbon fiber.

[0026] Preferably, the polyanion positive electrode material includes sodium vanadium phosphate and / or sodium vanadium fluorophosphate.

[0027] In a second aspect, the present invention provides a method for preparing the positive electrode sheet as described in the first aspect, the preparation method comprising the following steps:

[0028] (1) coating the first active layer slurry on at least one side of the current collector surface, and after drying, obtaining the first active layer on at least one side of the current collector surface;

[0029] (2) coating the second active layer slurry on the surface of the first active layer in step (1), and after drying, obtaining a coating on at least one side of the current collector, and obtaining the positive electrode sheet;

[0030] The first active layer slurry includes a first Prussian cathode material, and the second active layer slurry includes a polyanion cathode material;

[0031] In the coating, the content of the first Prussian cathode material is less than the content of the polyanion cathode material.

[0032] In a third aspect, the present invention provides a battery, comprising the positive electrode sheet as described in the first aspect, or the positive electrode sheet prepared by the preparation method as described in the second aspect.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The present invention uses a first Prussian positive electrode material in the inner first active layer to increase the capacity of the battery cell, and uses a polyanion positive electrode material in the outer second active layer, so that the positive electrode plate has good thermal stability and cycle stability and increases the capacity of the battery cell;

[0035] (2) A small amount of the second Prussian cathode material is added to the outer second active layer of the present invention, which further increases the capacity of the battery and prevents trace water in the air and the electrolyte from entering the inner layer and being absorbed by the first Prussian cathode material, causing structural collapse and affecting the gram capacity and stability;

[0036] (3) The present invention comprehensively improves the capacity and cycle performance of the sodium ion battery by adjusting the different ratios of the positive electrode materials in the first active layer and the second active layer;

[0037] (4) Since the embedding and insertion of the first active layer are slower than those of the outer layer, the conductive agent of the first active layer uses multi-walled carbon nanotubes to increase the lithium ion transfer rate, and the conductive agent of the second active layer uses non-multi-walled carbon nanotubes;

[0038] (5) The present invention constructs a functional relationship between the positive electrode main material and the water absorbent to obtain the optimal formula range; by adjusting different formulas and different thicknesses, the discharge capacity and cycle performance of the battery cell are improved;

[0039] (6) The preparation process of the present invention is simple and can be industrialized. DETAILED DESCRIPTION

[0040] In order to solve the problem that the capacity, thermal stability and cycle stability of existing batteries cannot be taken into account at the same time, the present invention adopts a first Prussian cathode material as an active material in the first active layer and a polyanion cathode material as an active material in the second active layer to simultaneously improve the capacity, thermal stability and cycle stability of the sodium ion battery.

[0041] In a specific embodiment, the present invention provides a positive electrode plate, the positive electrode plate comprising a current collector and a coating disposed on at least one side of the current collector, the coating comprising a first active layer disposed on the surface of the current collector, and a second active layer disposed on a side of the first active layer away from the current collector;

[0042] The first active layer includes a first Prussian cathode material, and the second active layer includes a polyanion cathode material;

[0043] In the coating, the content of the first Prussian cathode material is less than the content of the polyanion cathode material.

[0044] The present invention arranges a plurality of active layers on the positive electrode plate, arranges a first active layer including a first Prussian positive electrode material in an inner layer close to the current collector to improve the capacity of the battery, and arranges a second active layer including a polyanion positive electrode material in an outer layer away from the current collector to improve the thermal stability and cycle stability of the battery. In addition, since the first active layer and the second active layer are located at different positions and the transmission rates of ions and / or electrons are different, the content of the first Prussian positive electrode material in the present application is less than the content of the polyanion positive electrode material, thereby simultaneously improving the capacity, thermal stability and cycle stability of the battery.

[0045] Preferably, the mass ratio of the first Prussian cathode material to the polyanion cathode material is (1-3):(4-9), for example, 1:9, 2:5, 3:8, 3:4, 2:9 or 1:4, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] The mass ratio of the first Prussian cathode material to the polyanion cathode material of the present invention will affect the capacity and stability, so that the first Prussian cathode material in the first active layer plays a role in improving the capacity. If the first Prussian cathode material is too little, the capacity will be improved less, but if the first Prussian cathode material is too much, the cycle performance will be affected. The polyanion cathode material in the second active layer plays a role in improving thermal stability and cycle stability. If the ratio is too little, the cycle performance will be improved less, and if the ratio is too much, the capacity will be insufficient.

[0047] Preferably, the second active layer further includes a water absorbent.

[0048] The present invention adds a water absorbent in the second active layer to absorb water, thereby preventing trace water in the air and the electrolyte from entering the first active layer and being absorbed by the first Prussian cathode material, causing structural collapse and affecting gram capacity and stability.

[0049] Preferably, the mass ratio of the polyanion positive electrode material to the water absorbent is 20:(0.5-2), for example, 20:0.5, 20:1 or 20:2, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] The present invention adds a corresponding proportion of water absorbent, which can avoid the problem of excessive water absorbent causing the outer active material layer structure to collapse and the circulation capacity to decrease, and avoid adding too little water absorbent to prevent ineffective water absorption.

[0051] Preferably, the water absorbent includes a second Prussian cathode material.

[0052] The water absorbing agent of the present invention adopts the Prussian positive electrode material as the water absorbing agent, which can not only achieve the water absorbing effect, but also further improve the capacity of the battery.

[0053] Preferably, the mass ratio of the first Prussian positive electrode material to the polyanion positive electrode material is A, the mass fraction of the water absorbent / (the sum of the mass fractions of the first Prussian positive electrode material and the polyanion positive electrode material)×100 is B, and A and B satisfy the following relationship: B=e^[(bA) / a], wherein a is 0.8-0.9, for example, it can be 0.8, 0.85 or 0.9, and b is 0.8-1.87, for example, it can be 1, 1.5 or 1.87, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0054] The ratio of the active substances in the inner and outer layers of the present invention satisfies a specific functional relationship with the water absorbent. The water absorbent can absorb water, resist the attack of water on the active substances in the first active layer, and prevent the collapse of the active substance structure in the first active layer.

[0055] The smaller the value of A described in the present invention, the smaller the proportion of active substances in the first active layer, and the need to increase the active substances in the second active layer and add more water absorbents to prevent the active substances in the first active layer from being completely attacked by the generated water and losing the capacity improvement effect; as the value of A increases, the proportion of active substances in the first active layer increases, and the content of water absorbent in the second active layer can be appropriately reduced. At this time, the water absorbent resists most of the water attack. Although a small amount of water enters the first active layer, the excessive active substances in the first active layer are sufficient to resist the attack of water and the structure will not collapse. When the value of A continues to increase, the proportion of active substances in the first active layer further increases, and the ability to resist water attack without collapse is further increased, and the content of the required water absorbent can also be further reduced.

[0056] It should be noted that the value of A in the present invention cannot be too large, and the content of the water absorbent cannot be too small. When the value of A is too large and the content of the water absorbent is too small, a large amount of water enters the first active layer, which will also cause the collapse of the structure of the first active layer, thereby affecting the performance and stability of the gram capacity. Therefore, under the condition that the mass ratio A of the first Prussian positive electrode material to the polyanion positive electrode material is (1-3): (4-9), the ratio of the active material in the first active layer and the second active layer of the present invention presents an exponential relationship with the water absorbent.

[0057] When B is too small, a large amount of water absorption cannot be guaranteed, which may easily lead to the collapse of the first active layer structure; when B is too large, it will also have a certain impact on the structural stability of the second active layer.

[0058] Preferably, the mass fraction of the water absorbent is 2.25-9 parts, for example, 2.25 parts, 5 parts or 9 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0059] Preferably, the thickness ratio of the first active layer to the second active layer is (1-2):(2.25-3), for example, it can be 1:2.25, 1.5:2.5, 1:3 or 2:3, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0060] The thickness of the first active layer and the second active layer of the present invention needs to be controlled within a specific ratio. If the first active layer is too thin, the capacity advantage of the inner layer cannot be brought into play. If the outer second active layer is too thin, the cycle advantage cannot be brought into play. However, if the first active layer is too thick, the internal heat diffusion is poor, resulting in a decrease in the cycle capacity. At the same time, if it is too thick, the internal resistance of the battery cell increases, which is not conducive to the electrical performance.

[0061] Preferably, the first active layer further includes a first conductive agent.

[0062] Preferably, the second active layer further includes a second conductive agent.

[0063] Preferably, the sum of the mass fractions of the first conductive agent and the second conductive agent / (the sum of the mass fractions of the first Prussian positive electrode material and the polyanion positive electrode material)×100 is N, the thickness ratio of the first active layer and the second active layer is M, and M and N satisfy N=e^[(My) / x], wherein x is 0.12-0.13, for example, it can be 0.12, 0.125 or 0.13, and y is 0.15-0.25, for example, it can be 0.15, 0.2 or 0.25, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0064] The sum of the mass fractions of the conductive agent in the first and second active layers of the present invention and the change in the thickness ratio of the first and second active layers present a specific functional relationship, wherein the sum of the mass fractions of the conductive agent in the first and second active layers / (the sum of the mass fractions of the first Prussian positive electrode material and the polyanion positive electrode material)×100 is N, reflecting the amount of the double-layer conductive agent. The change in the thickness ratio M determines the ratio of the transmission distance of lithium ions. When M increases or decreases, the sum of the mass fractions N of the conductive agent in the first and second active layers also increases or decreases synchronously to adjust the transmission of lithium ions, thereby ensuring the battery capacity.

[0065] When the thickness ratio M is small, the lithium ion transmission in the first active layer is relatively easy. As the thickness ratio M increases, only a small increase in the amount of the double-layer conductive agent is required to ensure the battery capacity. When the thickness ratio M is large, the thickness ratio in the first active layer increases, and the lithium ion transmission in the first active layer is relatively difficult. As the thickness ratio increases, the amount of the double-layer conductive agent needs to be greatly increased to ensure the transmission of lithium ions, thereby ensuring the battery capacity. Therefore, M and N satisfy a specific exponential relationship.

[0066] Preferably, the first conductive agent includes any one of graphite, multi-walled carbon nanotubes, graphene, SP or acetylene black, or a combination of at least two thereof, preferably multi-walled carbon nanotubes.

[0067] Preferably, the second conductive agent includes any one of graphite, multi-walled carbon nanotubes, graphene, SP or acetylene black or a combination of at least two thereof, preferably any one of graphite, graphene, SP or acetylene black or a combination of at least two thereof.

[0068] Since the first active layer is located in the inner layer, its embedding and extraction are slower than those of the outer second active layer, so the conductive agent uses multi-walled carbon nanotubes to increase the transfer rate, and the outer conductive agent uses non-multi-walled carbon nanotubes. The non-multi-walled carbon nanotubes refer to conductive agents that do not include multi-walled carbon nanotubes, and their conductive properties are slightly lower than those of multi-walled carbon nanotubes, such as graphite, graphene, SP or acetylene black.

[0069] Preferably, the first active layer further includes a first binder.

[0070] Preferably, in the first active layer, the mass ratio of the first Prussian positive electrode material, the first conductive agent and the first binder is (10-40):(0.5-2):(0.3-1.2), for example, it can be 10:1:1, 20:0.5:0.3, 30:1.5:0.8 or 40:2:1.2, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0071] Preferably, the second active layer further includes a second binder.

[0072] Preferably, in the second active layer, the mass ratio of the polyanion positive electrode material, the second conductive agent and the second binder is (60-90):(2.4-3.6):(1.2-1.8), for example, it can be 60:2.4:1.2, 70:3:1.5 or 80:3.6:1.8, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0073] Preferably, the first Prussian positive electrode material includes any one or a combination of at least two of a Prussian white material, a Prussian blue material, a composite material of Prussian blue and activated carbon, a composite material of Prussian blue, chitosan and nanogold, and a composite material of Prussian blue, graphene and carbon fiber.

[0074] Preferably, the second Prussian positive electrode material includes any one or a combination of at least two of a Prussian white material, a Prussian blue material, a composite material of Prussian blue and activated carbon, a composite material of Prussian blue, chitosan and nanogold, and a composite material of Prussian blue, graphene and carbon fiber.

[0075] Preferably, the polyanion positive electrode material includes sodium vanadium phosphate and / or sodium vanadium fluorophosphate.

[0076] In another specific embodiment, the present invention provides a method for preparing a positive electrode sheet, the preparation method comprising the following steps:

[0077] (1) coating the first active layer slurry on at least one side of the current collector surface, and after drying, obtaining the first active layer on at least one side of the current collector surface;

[0078] (2) coating the second active layer slurry on the surface of the first active layer in step (1), and after drying, obtaining a coating on at least one side of the current collector, and obtaining the positive electrode sheet;

[0079] The first active layer slurry includes a first Prussian cathode material, and the second active layer slurry includes a polyanion cathode material;

[0080] In the coating, the content of the first Prussian cathode material is less than the content of the polyanion cathode material.

[0081] Preferably, in parts by mass, in the first active layer slurry of step (1), the number of the first Prussian-type positive electrode material is 10-40 parts, for example, 10 parts, 20 parts, 30 parts or 40 parts, the number of the first conductive agent is 0.5-2 parts, for example, 0.5 parts, 1 parts, 1.5 parts or 2 parts, the number of the first binder is 0.3-1.2 parts, for example, 0.3 parts, 0.5 parts, 1.0 parts or 1.2 parts, the number of the solvent is 15-25 parts, for example, 15 parts, 20 parts or 25 parts, but is not limited to the listed values, and other values ​​not listed within the numerical range are equally applicable.

[0082] Preferably, in parts by mass, in the second active layer slurry of step (2), the number of polyanion positive electrode materials is 60-90 parts, for example, 60 parts, 70 parts, 80 parts or 90 parts, the number of second conductive agent is 2.4-3.6 parts, for example, 2.4 parts, 3.0 parts or 3.6 parts, the number of second binder is 1.2-1.8 parts, for example, 1.2 parts, 1.5 parts or 1.8 parts, the number of solvent is 45-55 parts, for example, 45 parts, 50 parts or 55 parts, the number of water absorbent is 2.25-9 parts, for example, 2.25 parts, 5 parts or 9 parts, but is not limited to the listed values, and other values ​​not listed within the numerical range are equally applicable.

[0083] In another specific embodiment, the present invention provides a battery, which includes a positive electrode plate as described in a specific embodiment, or a positive electrode plate prepared by a preparation method as described in another specific embodiment.

[0084] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0085] Example 1

[0086] This embodiment provides a positive electrode plate, the positive electrode plate comprising an aluminum foil and a coating disposed on both sides of the aluminum foil, the coating comprising a first active layer disposed on the surface of the aluminum foil, and a second active layer disposed on a side of the first active layer away from the aluminum foil;

[0087] The first active layer comprises a first Prussian cathode material, multi-walled carbon nanotubes and PVDF (polyvinylidene fluoride) in a mass ratio of 40:0.5:0.3, wherein the first Prussian cathode material is Prussian blue;

[0088] The second active layer comprises a polyanion positive electrode material, SP (conductive carbon black) and PVDF in a mass ratio of 60:2.4:1.2, wherein the polyanion positive electrode material is sodium vanadium phosphate;

[0089] The mass ratio of the first Prussian cathode material to the polyanion cathode material is 3:4.5, and the thickness ratio of the first active layer to the second active layer is 1:2.84;

[0090] The mass fraction of the multi-walled carbon nanotubes is 0.5 parts, the mass fraction of the SP is 2.4 parts, the sum of the mass fractions of the multi-walled carbon nanotubes and the SP / (the sum of the mass fractions of the first Prussian cathode material and the polyanion cathode material)×100 is N=2.9, the thickness ratio of the first active layer to the second active layer is M=0.35, and M and N satisfy N=e^[(My) / x], wherein x is 0.12 and y is 0.225;

[0091] The method for preparing the positive electrode sheet comprises the following steps:

[0092] (1) 40 parts of Prussian blue, 0.5 parts of multi-walled carbon nanotubes and 0.3 parts of PVDF were added with 25 parts of NMP (N-methylpyrrolidone), stirred to form a first active layer slurry, and the first active layer slurry was coated on both sides of the aluminum foil. After drying, a first active layer with a thickness of 80 mm was obtained on both sides of the aluminum foil;

[0093] (2) 60 parts of sodium vanadium fluorophosphate, 2.4 parts of SP and 1.2 parts of PVDF were added with 45 parts of NMP and stirred to form a second active layer slurry. The second active layer slurry was coated on the surface of the first active layer in step (1). After drying, a second active layer with a thickness of 227 mm was obtained to obtain the positive electrode sheet.

[0094] Example 2

[0095] This embodiment provides a positive electrode plate, the positive electrode plate comprising an aluminum foil and a coating disposed on both sides of the aluminum foil, the coating comprising a first active layer disposed on the surface of the aluminum foil, and a second active layer disposed on a side of the first active layer away from the aluminum foil;

[0096] The first active layer comprises a first Prussian cathode material, multi-walled carbon nanotubes and PVDF in a mass ratio of 25:1:0.7, wherein the first Prussian cathode material is Prussian blue;

[0097] The second active layer comprises a polyanion cathode material, SP and PVDF in a mass ratio of 75:3:1.5, wherein the polyanion cathode material is sodium vanadium phosphate;

[0098] The mass ratio of the first Prussian cathode material to the polyanion cathode material is 2:6, and the thickness ratio of the first active layer to the second active layer is 1:2.63;

[0099] The mass fraction of the multi-walled carbon nanotubes is 1 part, the mass fraction of the SP is 3 parts, the sum of the mass fractions of the multi-walled carbon nanotubes and the SP / (the sum of the mass fractions of the first Prussian cathode material and the polyanion cathode material)×100 is N=4, the thickness ratio of the first active layer to the second active layer is M=0.38, and M and N satisfy N=e^[(My) / x], wherein x is 0.124 and y is 0.21;

[0100] The method for preparing the positive electrode sheet comprises the following steps:

[0101] (1) adding 20 parts of NMP to 25 parts of Prussian blue, 1 part of multi-walled carbon nanotubes and 0.7 parts of PVDF, stirring to form a first active layer slurry, coating the first active layer slurry on both sides of an aluminum foil, and drying to obtain a first active layer with a thickness of 100 mm on both sides of the aluminum foil;

[0102] (2) Add 50 parts of NMP to 75 parts of sodium vanadium fluorophosphate, 3 parts of SP and 1.2 parts of PVDF, stir to form a second active layer slurry, apply the second active layer slurry on the surface of the first active layer in step (1), and after drying, obtain a second active layer with a thickness of 263 mm, thereby obtaining the positive electrode sheet.

[0103] Example 3

[0104] This embodiment provides a positive electrode plate, the positive electrode plate comprising an aluminum foil and a coating disposed on both sides of the aluminum foil, the coating comprising a first active layer disposed on the surface of the aluminum foil, and a second active layer disposed on a side of the first active layer away from the aluminum foil;

[0105] The first active layer comprises a first Prussian cathode material, multi-walled carbon nanotubes and PVDF in a mass ratio of 10:2:1.2, wherein the first Prussian cathode material is Prussian blue;

[0106] The second active layer comprises a polyanion cathode material, SP and PVDF in a mass ratio of 90:3.6:1.8, wherein the polyanion cathode material is sodium vanadium phosphate;

[0107] The mass ratio of the first Prussian cathode material to the polyanion cathode material is 1:9, and the thickness ratio of the first active layer to the second active layer is 1:2.3;

[0108] The mass fraction of the multi-walled carbon nanotubes is 2 parts, the mass fraction of the SP is 3.6 parts, the sum of the mass fractions of the multi-walled carbon nanotubes and the SP / (the sum of the mass fractions of the first Prussian cathode material and the polyanion cathode material)×100 is N=5.6, the thickness ratio of the first active layer to the second active layer is M=0.43, and the M and the N satisfy N=e^[(My) / x], wherein x is 0.13 and y is 0.21;

[0109] The method for preparing the positive electrode sheet comprises the following steps:

[0110] (1) 10 parts of Prussian blue, 2 parts of multi-walled carbon nanotubes and 1.2 parts of PVDF were added with 15 parts of NMP, stirred to form a first active layer slurry, and the first active layer slurry was coated on both sides of the aluminum foil. After drying, a first active layer with a thickness of 160 mm was obtained on both sides of the aluminum foil;

[0111] (2) Add 55 parts of NMP to 90 parts of sodium vanadium fluorophosphate, 3.6 parts of SP and 1.8 parts of PVDF, and stir to form a second active layer slurry. Apply the second active layer slurry on the surface of the first active layer in step (1). After drying, a second active layer with a thickness of 369 mm is obtained to obtain the positive electrode sheet.

[0112] Example 4

[0113] This embodiment provides a positive electrode plate, the positive electrode plate comprising an aluminum foil and a coating disposed on both sides of the aluminum foil, the coating comprising a first active layer disposed on the surface of the aluminum foil, and a second active layer disposed on a side of the first active layer away from the aluminum foil;

[0114] The first active layer comprises a first Prussian cathode material, multi-walled carbon nanotubes and PVDF in a mass ratio of 10:1:1.2, wherein the first Prussian cathode material is Prussian blue;

[0115] The second active layer comprises a polyanion cathode material, SP and PVDF in a mass ratio of 90:3.6:1.8, wherein the polyanion cathode material is sodium vanadium phosphate;

[0116] The mass ratio of the first Prussian cathode material to the polyanion cathode material is 1:9, and the thickness ratio of the first active layer to the second active layer is 1:2.84;

[0117] The mass fraction of the multi-walled carbon nanotubes is 1 part, the mass fraction of the SP is 3.6 parts, the sum of the mass fractions of the multi-walled carbon nanotubes and the SP / (the sum of the mass fractions of the first Prussian cathode material and the polyanion cathode material)×100 is N=4.6, the thickness ratio of the first active layer to the second active layer is M=0.35, and M and N satisfy N=e^[(My) / x], wherein x is 0.12 and y is 0.17;

[0118] The method for preparing the positive electrode sheet comprises the following steps:

[0119] (1) adding 15 parts of NMP to 10 parts of Prussian blue, 1 part of multi-walled carbon nanotubes and 1.2 parts of PVDF, stirring to form a first active layer slurry, coating the first active layer slurry on both sides of an aluminum foil, and drying to obtain a first active layer with a thickness of 80 mm on both sides of the aluminum foil;

[0120] (2) 90 parts of sodium vanadium fluorophosphate, 3.6 parts of SP and 1.8 parts of PVDF were added with 55 parts of NMP and stirred into a second active layer slurry. The second active layer slurry was coated on the surface of the first active layer in step (1). After drying, a second active layer with a thickness of 227 mm was obtained, thereby obtaining the positive electrode sheet.

[0121] Example 5

[0122] This embodiment provides a positive electrode plate, the positive electrode plate comprising an aluminum foil and a coating disposed on both sides of the aluminum foil, the coating comprising a first active layer disposed on the surface of the aluminum foil, and a second active layer disposed on a side of the first active layer away from the aluminum foil;

[0123] The first active layer comprises a first Prussian cathode material, multi-walled carbon nanotubes and PVDF in a mass ratio of 10:1:1.2, wherein the first Prussian cathode material is Prussian blue;

[0124] The second active layer includes a polyanion cathode material, SP and PVDF in a mass ratio of 90:3.6:1.8, wherein the polyanion cathode material is sodium vanadium phosphate, the second active layer also includes a water absorbent, the water absorbent is Prussian blue, and the mass ratio of the polyanion cathode material to the water absorbent is 20:1;

[0125] The mass ratio of the first Prussian cathode material to the polyanion cathode material is A, A=0.11, the mass fraction of the water absorbent / (the sum of the mass fractions of the first Prussian cathode material and the polyanion cathode material)×100 is B, B=4.5, and A and B satisfy the following relationship: B=e^[(bA) / a], wherein a=0.823, b=1.35;

[0126] The mass ratio of the first Prussian cathode material to the polyanion cathode material is 1:9, and the thickness ratio of the first active layer to the second active layer is 1:2.84;

[0127] The mass fraction of the multi-walled carbon nanotubes is 1 part, the mass fraction of the SP is 3.6 parts, the sum of the mass fractions of the multi-walled carbon nanotubes and the SP / (the sum of the mass fractions of the first Prussian cathode material and the polyanion cathode material)×100 is N=4.6, the thickness ratio of the first active layer to the second active layer is M=0.35, and M and N satisfy N=e^[(My) / x], wherein x is 0.12 and y is 0.17;

[0128] The method for preparing the positive electrode sheet comprises the following steps:

[0129] (1) adding 15 parts of NMP to 10 parts of Prussian blue, 1 part of multi-walled carbon nanotubes and 1.2 parts of PVDF, stirring to form a first active layer slurry, coating the first active layer slurry on both sides of an aluminum foil, and drying to obtain a first active layer with a thickness of 80 mm on both sides of the aluminum foil;

[0130] (2) 90 parts of sodium vanadium fluorophosphate, 4.5 parts of water absorbent Prussian blue, 3.6 parts of SP and 1.8 parts of PVDF were added with 55 parts of NMP and stirred to form a second active layer slurry. The second active layer slurry was coated on the surface of the first active layer in step (1). After drying, a second active layer with a thickness of 227 mm was obtained to obtain the positive electrode sheet.

[0131] Example 6

[0132] This embodiment provides a positive electrode plate, in which the mass ratio of the polyanion positive electrode material to the water absorbent is 20:0.5, the mass ratio of the first Prussian positive electrode material to the polyanion positive electrode material is A, A=0.11, the mass fraction of the water absorbent / (the sum of the mass fractions of the first Prussian positive electrode material and the polyanion positive electrode material)×100 is B, B=2.25, and A and B satisfy the following relationship: B=e^[(bA) / a], wherein a=0.9, b=0.84;

[0133] The preparation method of the positive electrode sheet is the same as that of Example 5 except that the water absorbent is 2.25 parts.

[0134] Example 7

[0135] This embodiment provides a positive electrode plate, in which the mass ratio of the polyanion positive electrode material to the water absorbent is 20:2, the mass ratio of the first Prussian positive electrode material to the polyanion positive electrode material is A, A=0.11, the mass fraction of the water absorbent / (the sum of the mass fractions of the first Prussian positive electrode material and the polyanion positive electrode material)×100 is B, B=9, and A and B satisfy the following relationship: B=e^[(bA) / a], wherein a=0.8, b=1.87;

[0136] The preparation method of the positive electrode sheet is the same as that of Example 5 except that the water absorbent is 9 parts.

[0137] Example 8

[0138] This embodiment provides a positive electrode plate, in which the mass ratio of the polyanion positive electrode material to the water absorbent is 20:0.2, the mass ratio of the first Prussian positive electrode material to the polyanion positive electrode material is A, A=0.11, the mass fraction of the water absorbent / (the sum of the mass fractions of the first Prussian positive electrode material and the polyanion positive electrode material)×100 is B, B=0.9, and A and B do not satisfy the following relationship: B=e^[(bA) / a], wherein a is 0.8-0.9, and b is 0.8-1.87;

[0139] The preparation method of the positive electrode sheet is the same as that of Example 5 except that the water absorbent is 0.9 parts.

[0140] Example 9

[0141] This embodiment provides a positive electrode plate, in which the mass ratio of the polyanion positive electrode material to the water absorbent is 20:2.5, the mass ratio of the first Prussian positive electrode material to the polyanion positive electrode material is A, A=0.11, the mass fraction of the water absorbent / (the sum of the mass fractions of the first Prussian positive electrode material and the polyanion positive electrode material)×100 is B, B=11.25, and A and B do not satisfy the following relationship: B=e^[(bA) / a], wherein a is 0.8-0.9, and b is 0.8-1.87;

[0142] The preparation method of the positive electrode sheet is the same as that of Example 5 except that the water absorbent is 11.25 parts.

[0143] Example 10

[0144] This embodiment provides a positive electrode plate, which is the same as that of Embodiment 5 except that the water absorbent is CaO.

[0145] Embodiment 11

[0146] This embodiment provides a positive electrode plate, in which the mass fraction of the multi-walled carbon nanotubes is 1 part, the mass fraction of the SP is 3.6 parts, the sum of the mass fractions of the multi-walled carbon nanotubes and the SP / (the sum of the mass fractions of the first Prussian positive electrode material and the polyanion positive electrode material)×100 is N=4.6, the thickness ratio of the first active layer and the second active layer is M=1, and the M and the N do not satisfy the formula N=e^[(My) / x], wherein x is 0.12-0.13, and y is 0.15-0.25, and the rest is the same as that of Embodiment 5;

[0147] The preparation method of the positive electrode plate is the same as that of Example 5 except that the thickness of the first active layer and the second active layer are both 150 mm.

[0148] Example 12

[0149] This embodiment provides a positive electrode plate, in which the mass fraction of the multi-walled carbon nanotubes is 1 part, the mass fraction of the SP is 3.6 parts, the sum of the mass fractions of the multi-walled carbon nanotubes and the SP / (the sum of the mass fractions of the first Prussian positive electrode material and the polyanion positive electrode material)×100 is N=4.6, the thickness ratio of the first active layer to the second active layer is M=0.25, and the M and the N do not satisfy the formula N=e^[(My) / x], wherein x is 0.12-0.13, and y is 0.15-0.25, and the rest is the same as that of Embodiment 5;

[0150] The preparation method of the positive electrode plate is the same as that of Example 5 except that the thickness of the first active layer is 57 mm.

[0151] Embodiment 13

[0152] This embodiment provides a positive electrode plate, in which, except for the change in the content of the polyanion positive electrode material, the mass ratio of the first Prussian positive electrode material to the polyanion positive electrode material is 1:10, the mass ratio of the first Prussian positive electrode material to the polyanion positive electrode material is A, A=0.1, the mass fraction of the water absorbent / (the sum of the mass fractions of the first Prussian positive electrode material and the polyanion positive electrode material)×100 is B, B=4.5, and A and B satisfy the following relationship: B=e^[(bA) / a], wherein a is 0.823, b is 1.34, and the rest are the same as in Embodiment 5;

[0153] The preparation method of the positive electrode plate is the same as that of Example 5 except that the number of the polyanion positive electrode material is 100.

[0154] Embodiment 14

[0155] This embodiment provides a positive electrode plate, which is the same as that of Embodiment 5 except that the multi-walled carbon nanotubes are replaced with SP.

[0156] Comparative Example 1

[0157] This comparative example provides a positive electrode sheet, the positive electrode sheet comprising an aluminum foil and an active coating disposed on both sides of the aluminum foil, the active coating comprising a first Prussian positive electrode material, multi-walled carbon nanotubes and PVDF in a mass ratio of 100:3:2, wherein the first Prussian positive electrode material is Prussian blue, and the thickness of the active coating is 307 mm;

[0158] The method for preparing the positive electrode sheet comprises the following steps:

[0159] 100 parts of Prussian blue, 3 parts of multi-walled carbon nanotubes and 2 parts of PVDF were added with 55 parts of NMP, stirred into slurry, and coated on both sides of aluminum foil to obtain an active coating with a thickness of 307 mm, thereby obtaining the positive electrode sheet.

[0160] Comparative Example 2

[0161] This comparative example provides a positive electrode plate, the positive electrode plate comprising an aluminum foil and an active coating disposed on both sides of the aluminum foil, the active coating comprising sodium vanadium fluorophosphate, multi-walled carbon nanotubes and PVDF in a mass ratio of 100:3:2, and the thickness of the active coating is 307 mm;

[0162] The method for preparing the positive electrode sheet comprises the following steps:

[0163] 100 parts of sodium vanadium fluorophosphate, 3 parts of multi-walled carbon nanotubes and 2 parts of PVDF were added with 55 parts of NMP, stirred into slurry, and coated on both sides of aluminum foil to obtain an active coating with a thickness of 307 mm, thereby obtaining the positive electrode sheet.

[0164] Comparative Example 3

[0165] This comparative example provides a positive electrode sheet, which is the same as Example 1 except that the content of the first Prussian positive electrode material and the polyanion positive electrode material is changed and the mass ratio of the first Prussian positive electrode material to the polyanion positive electrode material is 1:1;

[0166] The method for preparing the positive electrode plate is the same as that of Example 1 except that the number of the first Prussian positive electrode material is 50 parts and the number of the polyanion positive electrode material is 50 parts.

[0167] The positive electrode sheets, separators and negative electrode sheets obtained in the above embodiments and comparative examples are wound into a core, wherein the separator completely covers the positive electrode sheet and the negative electrode sheet, and then the core is placed in a metal shell or wrapped with an aluminum-plastic film and injected with an electrolyte, and finally a sodium ion battery is made through processes such as standing, forming, and capacity separation; wherein the preparation of the negative electrode sheet includes: mixing hard carbon, SP, and PVDF with an appropriate amount of NMP in a ratio of 93:4:3 to prepare a negative electrode slurry, coating it on an aluminum foil, drying it with air at 100°C, and cold pressing and cutting it into negative electrode sheets.

[0168] Cycle test: At 25°C, the prepared battery was charged to 4.2V at 1C constant current and constant voltage, with a cut-off condition of 0.05C; after standing for 60 minutes, it was discharged to 2.0V at 1C, and the above process was continued until the capacity decayed to 80% of the initial test capacity, and the number of cycles was recorded.

[0169] Battery discharge capacity: Take the battery's first cycle discharge capacity as the battery capacity. The test results are shown in Table 1:

[0170] Table 1

[0171] First cycle discharge capacity / Ah Number of cycles / n Example 1 149 1326 Example 2 142 1408 Example 3 128 1504 Example 4 132 1532 Example 5 135 1623 Example 6 133 1524 Example 7 135 1536 Example 8 133 1453 Example 9 134 1575 Example 10 130 1633 Embodiment 11 132 1581 Example 12 131 1572 Example 13 133 1557 Embodiment 14 127 1534 Comparative Example 1 153 1056 Comparative Example 2 101 1577 Comparative Example 3 150 1239

[0172] From Table 1 we can see that:

[0173] It can be seen from Example 1, Example 5 and Comparative Examples 1-3 that the present invention designs active layers on both sides, and the inner active layer adopts the first Prussian positive electrode material, the outer active layer adopts the polyanion positive electrode material, and the content of the first Prussian positive electrode material is less than the content of the polyanion positive electrode material, which can ensure the battery capacity and cycle performance at the same time; from Example 5 and Examples 6-9, the amount of water absorbent added will affect the battery performance, and there is a specific functional relationship between the amount of water absorbent added and the ratio of the inner and outer layer active substances, which can further improve the battery performance; from Example 5 and Example 10, it can be seen that the present invention uses Prussian materials as water absorbents, which can not only absorb water, It can also further improve the battery capacity; it can be seen from Example 5 and Examples 11-12 that the total content of the conductive agent of the present invention and the ratio of the active layer thickness have a specific functional relationship, which can ensure the transmission of lithium ions and further improve the first-cycle discharge capacity; it can be seen from Example 5 and Example 13 that the content of the first Prussian positive electrode material of the present invention is less than the content of the polyanion positive electrode material, but cannot be too small, otherwise it will affect the battery capacity; it can be seen from Example 5 and Example 14 that since the inner layer is embedded and embedded slower than the outer second active layer, the present invention preferably uses multi-walled carbon nanotubes in the inner layer and non-multi-walled carbon nanotubes in the outer layer to ensure the capacity and cycle performance of the battery.

[0174] In summary, the present invention provides a positive electrode plate and a preparation method and application thereof. The positive electrode plate uses different types of positive electrode materials in different active layers, and the content of the first Prussian positive electrode material is less than the content of the polyanion positive electrode material, so that the positive electrode plate can have good thermal stability, cycle stability and capacity at the same time.

[0175] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A positive electrode sheet, characterized in that: The positive electrode sheet includes a current collector and a coating disposed on at least one side of the current collector, wherein the coating includes a first active layer disposed on the surface of the current collector, and a second active layer disposed on a side of the first active layer away from the current collector; The first active layer includes a first Prussian cathode material, and the second active layer includes a polyanion cathode material; In the coating, the content of the first Prussian cathode material is less than the content of the polyanion cathode material.

2. The positive electrode sheet according to claim 1, characterized in that: The mass ratio of the first Prussian cathode material to the polyanion cathode material is (1-3):(4-9).

3. The positive electrode sheet according to claim 1 or 2, characterized in that: The second active layer also includes a water absorbent; Preferably, the mass ratio of the polyanion positive electrode material to the water absorbing agent is 20:(0.5-2); Preferably, the water absorbing agent comprises a second Prussian cathode material; Preferably, the mass ratio of the first Prussian positive electrode material to the polyanion positive electrode material is A, the mass fraction of the water absorbent / (the sum of the mass fractions of the first Prussian positive electrode material and the polyanion positive electrode material)×100 is B, and A and B satisfy the following relationship: B=e^[(bA) / a], wherein a is 0.8-0.9, and b is 0.8-1.

87.

4. The positive electrode sheet according to claim 1 or 2, characterized in that: The thickness ratio of the first active layer to the second active layer is (1-2):(2.25-3); Preferably, the first active layer further includes a first conductive agent; Preferably, the second active layer further includes a second conductive agent; Preferably, the sum of the mass fractions of the first conductive agent and the second conductive agent / (the sum of the mass fractions of the first Prussian positive electrode material and the polyanion positive electrode material)×100 is N, the thickness ratio of the first active layer and the second active layer is M, and M and N satisfy N=e^[(My) / x], wherein x is 0.12-0.13, and y is 0.15-0.

25.

5. The positive electrode sheet according to claim 4, characterized in that: The first conductive agent comprises any one of graphite, multi-walled carbon nanotubes, graphene, SP or acetylene black or a combination of at least two thereof, preferably multi-walled carbon nanotubes; Preferably, the second conductive agent includes any one of graphite, multi-walled carbon nanotubes, graphene, SP or acetylene black or a combination of at least two thereof, preferably any one of graphite, graphene, SP or acetylene black or a combination of at least two thereof.

6. The positive electrode sheet according to claim 4, characterized in that: The first active layer further includes a first binder; Preferably, in the first active layer, the mass ratio of the first Prussian cathode material, the first conductive agent and the first binder is (10-40):(0.5-2):(0.3-1.2); Preferably, the second active layer further comprises a second binder; Preferably, in the second active layer, the mass ratio of the polyanion positive electrode material, the second conductive agent and the second binder is (60-90):(2.4-3.6):(1.2-1.8).

7. The positive electrode sheet according to claim 1 or 2, characterized in that: The first Prussian positive electrode material includes any one or a combination of at least two of Prussian white material, Prussian blue material, a composite material of Prussian blue and activated carbon, a composite material of Prussian blue, chitosan and nano-gold, and a composite material of Prussian blue, graphene and carbon fiber.

8. The positive electrode sheet according to claim 1 or 2, characterized in that: The polyanion positive electrode material includes sodium vanadium phosphate and / or sodium vanadium fluorophosphate.

9. A method for preparing a positive electrode sheet according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: (1) coating the first active layer slurry on at least one side of the current collector surface, and after drying, obtaining the first active layer on at least one side of the current collector surface; (2) coating the second active layer slurry on the surface of the first active layer in step (1), and after drying, obtaining a coating on at least one side of the current collector, and obtaining the positive electrode sheet; The first active layer slurry includes a first Prussian cathode material, and the second active layer slurry includes a polyanion cathode material; In the coating, the content of the first Prussian cathode material is less than the content of the polyanion cathode material.

10. A battery, characterized in that: The battery comprises the positive electrode sheet as described in any one of claims 1 to 8, or the positive electrode sheet prepared by the preparation method as described in claim 9.

Citation Information

Cited By

  • Positive plate, preparation method thereof and battery

    CN121506869A